A Generic Current Mode Design for Multifunction Grounded Capacitor Filters Employing Log-Domain Technique - N. A. Shah; F. A. Khanday (Active and Passive Electronic Components)
A generic design (GD) for realizing an nth order log-domain multifunction filter (MFF), which can yield four possible stable filter configurations, each offering simultaneously lowpass (LP), highpass (HP), and bandpass (BP) frequency responses, is presented. The features of these filters are very simple, consisting of merely a few exponential transconductor cells and capacitors; all grounded elements, capable of absorbing the shunt parasitic capacitances, responses are electronically tuneable, and suitable for monolithic integration. Furthermore, being designed using log-domain technique, it offers all its advantages. As an example, 5th-order MFFs are designed in each case and their performances are evaluated through simulation. Lastly, a comparative study of the MFFs is also carried, which helps in selecting better high-order MFF for a given application.